Basement geology and its controls on the nucleation and growth of rift faults in the northern Campos Basin, offshore Brazil. (15th February 2021) - Strugale, Michael; Schmitt, Renata da Silva; Cartwright, Joe
Abstract: The rift phase of the Campos Basin developed during the Early Cretaceous on a heterogeneous crust comprising structures inherited from the Brasiliano‐Pan African tectonic events, mostly generated during the Neoproterozoic‐Cambrian amalgamation of western Gondwana blocks. The main rifting episode took place from the Hauterivian to the Barremian, then was succeeded by the transition and post‐rift (SAG) phases during the Aptian. Rift faults developed as a result of a progressive rotation of extension from E‐W to NW‐SE. The role of pre‐existing intra‐basement structures on the style and evolution of the rift faults was investigated using 3D high‐resolution seismic data, borehole logs and sidewall samples. Three seismic facies (SF1, SF2 and SF3) and three types of intra‐basement structures (Surfaces, Geobodies and Internal Reflections) were identified and mapped. They represent, respectively, contrasting levels of seismic anisotropy, interpreted as metamorphic foliation, and ductile shear zones that bound rock units with particular seismic facies signatures. Sidewall cores show that banded biotite‐gneiss is the predominant rock type in the eastern half of the study area, while more homogeneous granitoid is the dominant lithology on the west. Such a binary division of lithotypes is consistent with the distribution of mapped intra‐basement seismic facies and features. The contrasting basement heterogeneity across the study area is the major control in the strain distribution during rifting. Where the basement is highly heterogeneous, the pre‐existing fabric was selectively reactivated whenever its orientation was favourable, resulting in faults forming progressively as the extension direction rotates, whilst shallower low to very low angle basement fabric were cross‐cut by rift faults. Where the basement is homogeneous, only early formed faults remain active throughout the rifting. Abstract : 3D seismic survey and novel wellbore data were used to describe the basement geology and its controls in the nucleation and growth of faults during the Early Cretaceous rifting in the northern of Campos Basin (Brazil).